Dermatophytic flora of tinea capitis of eastern anatolia - Aksungur, Lutfullah (The Turkish Journal of Pediatrics, 1968)
In this study a total of 5375 patients with dermatoses was examined in a period of 15 months and of these, 380 (7.1 per cent) were diagnosed as Tinea capitis. Of the 380 cases, 170 were favus and 210 were other forms of T. capitis, 130 of these kerion.Positive cultures were obtained from 333 specimens. The fungus causing the highest percentage of these 333 cases was T. schoenleini, 43.5 per cent; this was followed by T. verrucosum, 27.3 per cent. The other fungi in order of their frequency were: M. canis, 16.5 per cent; T. violaceum, 10.5 per cent; and T. mentagrophytes, 2.5 per cent.In both Central and Eastern Anatolia the predominant fungus was T. schoenleini. The fungus second in order in Central Anatolia was T. violaceum as opposed to T. verrucosum in the East. T. violaceum increases in the number of cases that it produces as we move west to the point where it is the leading cause in the region near Istanbul. This is a clear indication of the regional variation of the dermatophytic flora of Turkey.Out of 170 cases of favus, T. violaceum was found to cause five. Two cases of mixed infection caused by T. schoenleini and T. violaceum were demonstrated. This is the first time that either infections by T. violaceum, in the form of favus, or mixed infections in T. capitis have been reported in Turkey.T. verrucosum was the major cause of kerion in Eastern Anatolia and M. canis was second. They were reversed with M. canis as the major cause in the case of noninflammatory T. capitis.Id reactions were seen more often in the kerion form, 18 out of 130 cases. Of these, 15 were due to T. verrucosum and most of the 15 were a diffuse follicular erythematous papular form.Auto-inoculation was not usually seen in the cases caused either by anthropophilic or zoophilic fungi. However, cross-infection between siblings occurred frequently in the T. capitis caused by T. schoenleini and T. violaceum. In the zoophilic infections, the family incidence was almost nonexistent.In all types of T. capitis, males were found to be affected at a much higher rate than females. The age group most commonly affected by favus was from five to 14 years and by the other two forms from five to nine years.Of the favus cases caused by T. schoenleini, 30 were observed after puberty, but in all of these the infection had begun before puberty and had continued for a long period of time. However, two cases of kerion were seen whose onset took place after puberty. One of these patients was 25 and the other 60 years of age and in both the site of the disease was the occipital area.